The Higher the Life Satisfaction, the Better the Psychological Capital? Life Satisfaction and Psychological Capital: A Moderated Mediation Model - Shan, Huanhuan; Ishak, Zahari; Fan, Liheng (Frontiers in Psychology, 2022)
This study investigates the mediator role of attachment avoidance and the moderator role of rejection sensitivity on the links between life satisfaction and psychological capital (PsyCap). This study uses the Experiences in Close Relationship Scale, Rejection Sensitive Scale, Positive Psychological Capital Scale, and Life Satisfaction Scale among 999 Chinese young adults as subjects. The results presented that life satisfaction had a significant positive predictive effect on PsyCap. Mediation analysis of this study shows that attachment avoidance mediated the association between life satisfaction and PsyCap. Furthermore, moderated mediation analysis indicated that rejection sensitivity moderates the link between life satisfaction and attachment avoidance (first-stage moderation). Compared with individuals with low rejection sensitivity, individuals with high rejection sensitivity show more attachment avoidance under low life satisfaction. This study helps understand the relationship between life satisfaction and PsyCap from the perspective of rejection sensitivity theory and attachment theory and has implications for guiding college students toward strengthening PsyCap and weakening rejection sensitivity.